Transformasi Literasi Karakter Melalui Komik Digital Interaktif Sebagai Inovasi Pembelajaran di Sekolah - Kinanti, Rani Agus; Asiah, Nur; Afriyadi, Muhammad Muchsin (Universtas Negeri Makassar, 2026)
The development of digital technology requires a transformation of character learning that aligns with the learning characteristics of elementary school students. However, character learning is still predominantly conventional and has not optimally utilized interactive digital media. This study aims to analyze the transformation of character literacy through interactive digital comics as a learning innovation in elementary schools. The research employed a Systematic Literature Review (SLR) based on PRISMA guidelines. Of the 243 identified articles, 7 articles were analyzed using bibliometric analysis with VOSviewer and thematic analysis. The results indicate that interactive digital comics effectively support the transformation of character literacy through the integration of reading, visual, and digital literacy, as well as increasing students’ learning interest and engagement. This study recommends the use of interactive digital comics in character learning in elementary schools.